KF addition to Cu2SnS3 thin films prepared by sulfurization process. (3rd February 2017) - Nakashima, Mitsuki; Fujimoto, Junya; Yamaguchi, Toshiyuki; Sasano, Junji; Izaki, Masanobu
Abstract: Cu2 SnS3 thin films were fabricated by sulfurization with KF addition and applied to photovoltaic devices. Two methods, two-stage annealing and the use of four-layer precursors, were employed, and the quantity of NaF and KF and the annealing temperature were changed. By electron probe microanalysis (EPMA), the Cu/Sn mole ratio was found to range from 0.81 to 1.51. The X-ray diffraction (XRD) patterns and Raman spectra indicated that the fabricated thin films had a monoclinic Cu2 SnS3 structure. The Cu2 SnS3 thin films fabricated by two-stage annealing had a close-packed structure and a pinhole-free surface morphology. The best solar cell in this study showed V oc of 293 mV, which surpassed the previously reported value.